Empowerment of TPQ through Integration of Digital Technology in Data Recording System and Monitoring of Student Learning Outcomes. - Kumalasari, Ellisia; Karaman, Jamilah; Masykur, Fauzan; Karaman, Lazuardi Irham (Abdimas Indonesian Journal, 2024)
This report addresses the challenges faced by TPQ Awwalul Huda in managing student data and monitoring learning outcomes, highlighting the need for improved efficiency and parental involvement in the educational process. The primary objective of this study is to develop a web-based student data recording system that enhances data management and facilitates real-time monitoring of student progress. The methods employed include a comprehensive needs analysis, system design, implementation, and socialization of the new system to 12 teachers and approximately 80 parents. The findings indicate that the newly implemented system significantly improves the efficiency of data management, allowing for better tracking of student performance and attendance. Additionally, it fosters greater engagement from parents, enabling them to monitor their children's learning outcomes more effectively. The study concludes that integrating digital technology into the educational framework of TPQ Awwalul Huda not only enhances transparency and accountability in managing student data but also contributes to the overall improvement of educational quality. This initiative demonstrates the potential of digital solutions in addressing the challenges faced by non-formal educational institutions, ultimately leading to a more effective and participatory learning environment for students and their families.